Anthropological methods for age estimation in cadavers or skeletal remains - Scaramussa, Fernanda Sobral (2019)
Introduction: The word anthropology derives from the Greek and means the science that studies the cultural and biological aspects of human beings. In forensic medicine, it helps identify the individual by determining the biological profile: ethnicity, sex, age, and height. Of these, one of the most important, in unidentified bodies, is the age. Objectives: To describe the most used methods to estimate post-mortem age as well as recent advances. Methods: Literature review of articles from Pubmed, Lilacs, and academic websites from 1920 to 2019. Results: The age estimation methods for skeletonized and dental elements were reviewed. Cranial sutures are more accurately evaluated in isolation. As for the mandible, the examination of the formed angle is fundamental for the estimation. Regarding the pelvic bone methods, the Suchey-Brooks method is more accurate than Todd's and the Two Step Procedure technique is the most accurate. For the coastal arches, Kunos has the best accuracy. In the context of “virtual anthropology”, the nuclear magnetic resonance is the most appropriate tool. The analysis of the sternum showed a variation of only 5.88 years and the use of the acetabulum was the most accurate for a 10-year interval. Discussion: Forensic anthropology is an area affected mainly by difficulties in standardizing the methods. Despite the description of several studies that estimate age, many are equivalent, such as Lovejoy and Suchey Brooks. In addition, most share the same limitations, such as the difficulty in estimating ages over 70. Another important issue is that the methods are specific to the studied population. So, when they are applied to different samples, the accuracy is significantly reduced: from 83-100% to 30-56% (acetabulum studies). Therefore, the age estimate should be made by association of methods to obtain better results. Conclusion: The most used methods are analysis of cranial sutures, angle of the mandible, pelvic bones, rib bones and teeth. The most recent methods are “virtual anthropology” and the study of the sternum.